META ANALISIS DETERMINAN PENGHINDARAN PAJAK - Swandi, Elsya Dinda; Prasetyo, Arihadi (Jurnal Akuntansi, 2024)
In the companies point of view tax is a burden that potentioal reduce the profits of the company itself. There is a lot of effort minimize tax such as  tax avoidance , one of the efforts used by tax payers to avoid taxes using legal methods with the aim of minimizing the amount of  individual or corporate tax payable.There are so many factor dirven the motive to do it. The purpose of this research was to examine the effect of profitability, leverage, firm size, institusional ownership, and sales growth on tax avoidance.Study Literatur Rerearch utilize inconducting this research. The object of this research uses secondary data in comprises research publish  from 26 journals that are integrated with SINTA. The data analysis methods used in this research is meta- analysis. Base on the research analysist can be withdrawn conclusions of this study as are follow: The variable of profitability, leverage, company size, institusional ownership, and sales growth significant influence tax avoidanve.